PG3 A major haemorrhage simulation during the COVID-19 pandemic. (10th November 2020) - Shah, Ashoke; Rowson, Mark; Harrison, Liam; Bidwai, Anita
Abstract : Introduction: The Government decided that during the COVID pandemic, prioritisation should be given to patients requiring urgent cancer surgery. 1 To enable this, 'COVID free hubs' are required and the Cheshire and Merseyside Alliance has been established. St Helens Hospital, the surgical day case unit of St Helens & Knowsley Hospitals Trust, has been designated the regional surgical hub for major urological and colorectal cancers. Methods: We conducted a transparent in-situ major haemorrhage simulation, on a patient who had undergone major abdominal surgery. They subsequently required re-exploration and management in theatre. The rationale behind this simulation was the implementation of major abdominal surgery, staff unfamiliarity to the site and each other, no on site transfusion laboratory and within a previous day case unit. We conducted a pre and post simulation questionnaire based on confidence and knowledge. We also conducted a thorough post scenario debrief with expertise from the blood transfusion practitioner. Results: 11 participants were involved in the simulation. 54% (6/11) were confident that the 'covid free cancer hub' would be a success and 54% (6/11) were confident in dealing with a major haemorrhage. The main concerns included, location of equipment, no transfusion or ITU on site and concerns for patient safety if the patient deteriorated overnight. Of the post simulation responses, all participants felt more confident in dealing with major haemorrhage and found the simulation extremely useful. Take home messages included, taking ownership of delegated task, identifying location of emergency blood, requirement for a co-ordinator and effective communication. Discussion: The in-situ simulation on major haemorrhage was very well received. During the debrief we discussed the importance of following the Standard Operating Procedures, the HALT tool, a delegated person to have discussions with transfusion and a co-ordinator to oversee, as there was communication mainly within subgroups. A communication board is required and dedicated scribe to document timings of drug and blood product administration. It took 45 minutes from the first communication with the transfusion laboratory (as blood is dispatched in a taxi) until the first group specific blood was administered. There was a delay of 28 minutes in administering O Negative blood due to the nurse having difficulties with locating the blood fridge, using the kiosk and blood tracking system. Recommendations: Regular in situ simulation at the St Helens site, Knowledge on transfusion could be improved further, Improve communication and familiarity with the HALT tool. References: NHS England and NHS Improvement, 2020. Clinical Guide For The Management Of Essential Cancer Surgery For Adults During The Coronavirus Pandemic . [online] NHS England; Royal College of Surgeons; British Association of Surgical Oncology. Available at: <https://www.england.nhs.uk/coronavirus/publication/clinical-guide-for-the-management-of-essential-cancer-surgery-for-adults-during-the-coronavirus-pandemic/> [Accessed 15 May 2020].